Analisis Sebaran Tingkat Kriminalitas dan Faktor-Faktor Penyebab di Kota Jayapura - Kesya S. Pongtiku; Irja Tobawan Simbiak; Riano Martez Rumbiak (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Crime represents unlawful acts contrary to societal norms. In 2021, Jayapura City experienced a high number of criminal cases, predominantly involving crimes against property and goods. This study maps the distribution of crime rates and identifies contributing factors in Jayapura City using the K-Means Clustering and Analytical Hierarchy Process (AHP) methods. K-Means Clustering analysis revealed five crime levels: high, relatively high, moderate, quite low, and low. North Jayapura District exhibited the highest crime rates among all districts, with Gurabesi Village similarly showing elevated criminal activity. The clustering results were subsequently mapped to visualize the spatial distribution patterns of crime. AHP analysis identified economic factors and low educational attainment as primary contributors to criminal behavior in Jayapura City. Among various intervention alternatives, job creation emerged as the most effective strategy, achieving the highest comparative value for simultaneously improving educational quality and security conditions. These findings provide crucial insights for law enforcement agencies and policymakers to develop targeted crime prevention strategies, focusing on economic development and educational improvement in high-risk areas, particularly North Jayapura District and Gurabesi Village.